THE EFFICACY COMPARISON OF MIRABEGRON AS A MONOTHERAPY VERSUS ITS COMBINATION WITH SOLIFENACIN IN OVERACTIVE BLADDER: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - Madani, Hasan; Soetojo; Djatisoesanto, Wahjoe (Indonesian Journal of Urology, 2021)
Objective: This review aimed to evaluate the efficacy and safety of mirabegron as monotherapy and its combination with solifenacin for patients with overactive bladder (OAB). Material & Methods: A systematic search was conducted in PubMed, Google Scholar, and Science Direct using the keywords Overactive bladder or OAB and mirabegron or beta-3 agonist or β3 adrenoreceptor agonist and solifenacin or antimuscarinic based on the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guideline to include relevant randomized controlled trials (RCT)s. The included studies were assessed for their risks of bias using the Cochrane risk of bias tool for randomized controlled trials. Quantitative analysis using forest plot was performed in Review Manager 5.4. Results: A total of 4 RCTs were included from 227 studies. A fixed-effects model was chosen due to the low level of heterogeneity between the studies (I2 = 0%). The average micturition volume of patients in the combination group is higher compared to the monotherapy group (MD 17.13, 95% CI 12.78 - 21.48, p < 0.00001). The mean micturition frequency (MD - 0.54, 95% CI - 0.73 - -0.34, p < 0.00001) and incontinence incidence (MD -0.30, 95% CI -0.48 - -0.12, p = 0.001) in the combined group are significantly lower compared to the monotherapy group. Conclusion: The combination of mirabegron and solifenacin has better efficacy compared to mirabegron as monotherapy for OAB patients with a therapy duration of less than 12 weeks based on the micturition volume, micturition frequency, and incontinence incidence. The administration of combination therapy would not increase adverse event incidence compared to monotherapy.